Residents as learning facilitators inside and outside of interprofessional education: a faculty development program in postgraduate pediatric training - Müller, Philipp A.; Straub, Christine; Heinzmann, Andrea; Langer, Thorsten; Bode, Sebastian F. N.; Griewatz, Jan; Kimmig, Christian; Friedrich, Sebastian (Frontiers in Medicine, 2025)
IntroductionChanging learning environments in health professions are an important challenge of interprofessional education (IPE). When students experience IPE activities during their undergraduate training, they are often guided by trained learning facilitators. Students still spend more time in non-IPE settings, often guided by residents. Residents rarely undergo specific training for core teaching competencies that are crucial in both IPE and non-IPE contexts. At our pediatric hospital, some residents were trained as learning facilitators on an interprofessional training ward. To bridge the gap between IPE and non-IPE learning facilitation for the other residents, we developed the resident-as-teachers course “How to teach pediatrics.”Methods“How to teach pediatrics” was implemented as a 4-week blended learning program based on the framework of Core Competencies for Medical Teachers (KLM). The intended learning outcomes were to reflect on residents’ role modelling and professionalism as well as personal teaching practice, emphasize learner centeredness and foster social and communicative competencies. Participants self-assessed their teaching competencies pre/post-course using a validated questionnaire (FKM_L). Oral feedback was gathered by group reflection and qualitative feedback by open-ended survey questions.Results26 residents participated in the course, of which N = 22 qualified for the pre/post-course self-assessment via the FKM_L (return rate: n = 9; 40.9%). Participants reported an increase in the competency fields of “didactical activities in medicine,” “social and communicative competence,” “role model and professional behavior” as well as “reflection and further development of own teaching practice.” Participants evaluated the course overall as “very good,” stated a high learning gain and estimated the course to be a good preparation for teaching students.Discussion“How to teach pediatrics” shows the feasibility of integrating faculty development as part of resident training. We observed a self-assessed increase in core competencies for medical teachers after participating in the course. Although more participants need to be included and long-lasting effects still need to be proven, such faculty development programs for learning facilitators might be an opportunity to ensure a more consistent and high-quality learning experience for students in both IPE and non-IPE teaching and learning activities.